Comparison of Efficacy of Lidocaine Vs. Fentanyl in Reducing Hemodynamic Response to Endotracheal Intubation - Tahir Ali, Zahid Aziz Soomro, Syed Farjad Sultan, Ashok Perchani (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the mean change in hemodynamics between patients undergoing endotracheal intubation with lidocaine vs fentanyl. Design of the Study: randomized controlled trial. Study Settings: This study was conducted at Department of Anaesthesiology, SICU and Pain Management, Civil Hospital Karachi, Dow University of Health Sciences from 21 September 2019 to 21 March 2020. Material and Methods: A total of 92 patient’s elective surgery was randomly allocated into two groups, 46 Patients in group A were treated with lidocaine and 46 in group B were treated with fentanyl. Heart rate and MAP was recorded 5 minutes post-intubation by independent observer (postgraduate trainee 1-2 years). Results of the Study: Attenuating the hemodynamic response was most successfully accomplished by administering IV fentanyl 3 g/kg 5 minutes prior to induction, in our case. Conclusion: Attenuating the hemodynamic response was most successfully accomplished by administering IV fentanyl 3 g/kg 5 minutes prior to induction, in our case. It is a standard aspect of anaesthetic care and has been shown to reduce the hemodynamic response to laryngoscopy and intubation in a safe and effective manner.